PKM PELATIHAN PEMOGRAMAN DENGAN MENGGUNAKAN SMART RELAY DI SMK NEGERI 2 SUNGAILIAT BANGKA - yudhi yudhi; ocsirendi ocsirendi (Jurnal Pengabdian Masyarakat Polmanbabel, 2022)
Polman Bangka-Belitung is one of the Polytechnics in Bangka-Belitung Province, where the output of this graduate is an engineer in the field of electrical engineering, design and machining. With the support of equipment and experienced lecturers in the vocational field, one of the obligations of a lecturer is community service, where the main purpose of this service is to apply knowledge and technology that can improve the welfare of the community both in the campus environment in particular and the people of Bangka. In general, the method used in this process is by using a quantitative method, namely applying direct observations of conditions in the field or in other words in real terms of taking data in the field. And one of the service programs is to provide training using smart relays, based on a survey we did where almost 95% of the students of SMK Negeri 2 Sungailiat Bangka Induk have not been able to understand about smart relay programming as a whole, so they need training that leads to the competencies they have in accordance with the standar of the National Professional Certification Agency, as well as in the manufacturing industry.